Demand-side approaches: Supporting healthier food choices - Kim, Sunny S.; Koyratty, Nadia; Blake, Christine E.; Kumar, Neha (International Food Policy Research Institute, 2024)
Understanding individual food choices and their net aggregate — which constitutes demand — is essential for any effort to reshape food systems to achieve broad nutrition and sustainability goals. This chapter presents an overview of food choice and consumer food demand in complex food systems, provides a summary of evidence for demand-side approaches to improve the healthfulness of diets, and identifies key areas where demand-side approaches can foster healthier food choices to achieve optimal health and nutrition.